2004
DOI: 10.1029/2002rs002790
|View full text |Cite
|
Sign up to set email alerts
|

A method for determining intracloud lightning and ionospheric heights from VLF/LF electric field records

Abstract: [1] The Los Alamos Sferic Array (LASA) recorded VLF/LF electric-field-change signals from over ten million lightning discharges during the period from 1998 to 2001. Using the differential-times-of-arrival of lightning sferics recorded by three or more stations, the latitudes and longitudes of the source discharges were determined. Under conditions of favorable geometry and ionospheric propagation, sensors obtained ionospherically reflected skywave signals from the lightning discharges in addition to the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
204
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(240 citation statements)
references
References 25 publications
22
204
1
Order By: Relevance
“…Modification 2: Our model imposes a fixed low-pass filter on the input (groundwave) waveform. Rather than generate an echo model using a partially-conducting reflector (Smith et al, 2004), our present approach is to impose a frequency roll-off that is found to work better than the approach of Smith et al at mimicking the data, over the majority of events analyzed. By this, we mean that the modified approach results in a modeled ionospheric echo that more closely resembles the observed ionospheric echo, relative to that of an echo model using a partially-conducting reflector (Smith et al, 2004).…”
Section: Reflection Model and Height Retrievalmentioning
confidence: 99%
See 4 more Smart Citations
“…Modification 2: Our model imposes a fixed low-pass filter on the input (groundwave) waveform. Rather than generate an echo model using a partially-conducting reflector (Smith et al, 2004), our present approach is to impose a frequency roll-off that is found to work better than the approach of Smith et al at mimicking the data, over the majority of events analyzed. By this, we mean that the modified approach results in a modeled ionospheric echo that more closely resembles the observed ionospheric echo, relative to that of an echo model using a partially-conducting reflector (Smith et al, 2004).…”
Section: Reflection Model and Height Retrievalmentioning
confidence: 99%
“…The two vertical dashed lines indicate the expected echo-arrival times for, respectively, the ionospheric and the ground-then-ionospheric echoes, based on a model which assumes a discrete mirror at an ionospheric height H i =61.2 km and a source height H s =13.1 km. The standard LASA height-retrieval (Smith et al, 2004) uses this approach and has obtained serviceable estimates of H s for lightning research. The standard retrieval idealizes the ionosphere as a sharp boundary between vacuum (underneath) and a finiteconductivity (e.g., 2.2 micro-mhos/m, as recommended by VLF experience (Wait and Spies, 1964)), isotropic conductor.…”
Section: Reflection Model and Height Retrievalmentioning
confidence: 99%
See 3 more Smart Citations